Age-related differences in affective and cognitive empathy: self-report and performance-based evidence. Issue 5 (3rd September 2018) - Sun, Binghai; Luo, Zhenbing; Zhang, Wenwen; Li, Weijian; Li, Xinyu
ABSTRACT: The correlation between age and empathy is not clear, with prior findings yielding mixed and inconsistent results. Here, we distinguished between two aspects of empathy and respectively investigated the effects of age on the affective and cognitive facets of empathy using a self-report measure (interpersonal reactivity index, IRI) and performance-based tasks (viewing films). The results showed that older adults manifested age-related deficits in both trait and state cognitive empathy, with the latter being positively associated with memory. Otherwise, the overall affective empathy increased in the elderly, but the age-related differences in affective empathy may be qualified by the valence of the film clips. Specifically, older participants showed more empathic concern (EC) and less personal distress (PD) to other people's emotions than the younger participants for the distress film. Interestingly, for the amusing film, older participants demonstrated more EC and PD. Overall, the two aspects of empathy have different development trajectories.